EXPLORING CATUR GURU VALUES IN CLASSROOM INTERACTION: A PEDAGOGICAL DISCOURSE ANALYSIS OF THE SUWINDIA MODEL IN HINDU RELIGIOUS EDUCATION - A A Pt Suari; I Gede Suwindia; Ni Nyoman Kurnia Wati; Ni Putu Dian Utami Dewi; I Made Hendra Sukmayasa (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Hindu religious education in elementary schools often remains normative, providing limited space for critical dialogue, even though the teachings of Catur Guru contain essential values for shaping students’ character. This study emphasizes a pedagogical discourse analysis of the implementation of the SUWINDIA model, which is integrated with the Hindu epistemology of Catur Pram??a. The research employs a descriptive qualitative approach within Fairclough’s Critical Discourse Analysis framework, encompassing the dimensions of text, discourse practice, and social practice. Data were collected through participatory observation, in-depth interviews, and document analysis of Catur Guru textbooks. The findings reveal that, at the textual dimension, teachers employ religious vocabulary, metaphors, and cohesion to instill spiritual values; at the level of discourse practice, teacher–student interactions recontextualize the values of Catur Guru through discussion, instruction, and reflection; whereas at the level of social practice, learning functions as a medium for the internalization of devotion, discipline, and spiritual awareness. The implementation of SUWINDIA is shown to align with Catur Pram??a, as it encourages students to learn through direct experience, reasoning, analogy, and sacred teachings. This study contributes to the development of Hindu religious education models that are more dialogical, reflective, and applicable in primary education